INFLATION AND ACCELERATION OF UNIVERSE FROM NONMINIMAL COUPLING GRAVITY AND NONLINEAR ELECTRODYNAMICS - Fitrah Izzah, Ramy
The inflationary universe is proposed to explain several problems in the conventional Big Bang theory, such as horizon, monopole, and flatness problems. There have been many models of inflation proposed, but until recently no one knew how inflation actually happened in the early universe. In addition, the results of observations of Type Ia Supernovae (SN Ia) show that the expansion of the universe is accelerating. The cause of this accelerated expansion of the universe is still unknown for certain, it is one of the greatest mysteries in modern cosmology. In this research we propose a model of gravity that is nonminimally coupled with nonlinear electrodynamics to find a solution for an inflationary universe in early-time. We also consider the cosmological constant (?) in Einstein’s equations to obtain a solution for the acceleration of the universe in late-time. This research begins by considering the action integral of the model. Then the action is varied with respect to the metric to obtain the dynamics equations of the universe. We study the evolution of the universe by finding the solutions to dynamical equations. From the evolution of the scale factor a(t) equation, it is found that the scale factor a(t) only approach 0 when t ? ??. This model describes the inflation of the universe with a scale factor that expands exponentially in early-time. Then from the evolution of the equation of state parameter w, it is found that the value of w = ?2/3 in late-time, this fulfills the conditions for a universe experiencing accelerated expansion in late-time.